MENDIOLA, I. (2022). El poder y la caza de personas. Frontera, seguridad y necropolítica. Barcelona: Bellaterra Edicions, 301 pp. - Zubero, Imanol (Daimon Revista Internacional de Filosofia, 2022)
Reseña de: MENDIOLA, I. (2022). El poder y la caza de personas. Frontera, seguridad y necropolítica. Barcelona: Bellaterra Edicions, 301 pp.